Acceptability of Children with Special Needs in the Inclusive Elementary School - Muhammad Ragil Kurniawan; Nurul Hidayati Rofiah (Journal of Education and Learning (EduLearn), 2018)
The main obstacle of children with special needs to advance is access to education as high as possible not to the disability, but to social acceptance of the community. This study aims 1) To determine the acceptability of children with special needs in the inclusive elementary school environment. It includes principals, teachers, learners, and parents. 2) To determine the factors those influence the acceptance of children with special needs in the inclusive elementary school environment. This is an interactive qualitative research. The research site is Wirosaban Elementary School, Yogyakarta City. Data collection techniques are interviews, observation and documentation. Data analysis technique is analytic descriptive data analysis. The results show: 1) Acceptability of children with special needs in inclusive school environment is quite good after going through various processes. School trying to accept children with special needs even though the school realized its service on some things still not maximal 2) There are four factors that affect the school environment perception of children with special needs. These factors are: knowledge and insight factor on inclusive education, b. environmental support factor outside the school, c. facilities factor, d. the persistence factor of the guardians of the special needs students.